2018
DOI: 10.3390/ijerph15040727
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Residential Exposure Risk from Spills of Flowback Water from Marcellus Shale Hydraulic Fracturing Activity

Abstract: Identifying sources of concern and risk from shale gas development, particularly from the hydraulic fracturing process, is an important step in better understanding sources of uncertainty within the industry. In this study, a risk assessment of residential exposure pathways to contaminated drinking water is carried out. In this model, it is assumed that a drinking water source is contaminated by a spill of flowback water; probability distributions of spill size and constituent concentrations are fit to histori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…4 Analyses of ground and surface water samples near hydraulic fracturing sites have identified chemicals and by-products associated with hydraulic fracturing fluids and wastewater, including volatile organic compounds 5,6 and halides, 7,8 with spills and leakage representing possible contaminant pathways. [9][10][11] In 2016, the US Environmental Protection Agency (EPA) published a report on several mechanisms through which hydraulic fracturing fluids and associated wastewater might impact water supplies. 12 Furthermore, the EPA compiled oral toxicity data for chemicals in hydraulic fracturing fluids and found that 986 (91%) of 1084 did not have the evidence required to identify maximum safe chronic oral reference dose values.…”
Section: Introductionmentioning
confidence: 99%
“…4 Analyses of ground and surface water samples near hydraulic fracturing sites have identified chemicals and by-products associated with hydraulic fracturing fluids and wastewater, including volatile organic compounds 5,6 and halides, 7,8 with spills and leakage representing possible contaminant pathways. [9][10][11] In 2016, the US Environmental Protection Agency (EPA) published a report on several mechanisms through which hydraulic fracturing fluids and associated wastewater might impact water supplies. 12 Furthermore, the EPA compiled oral toxicity data for chemicals in hydraulic fracturing fluids and found that 986 (91%) of 1084 did not have the evidence required to identify maximum safe chronic oral reference dose values.…”
Section: Introductionmentioning
confidence: 99%
“…To put these data into perspective, we surveyed organohalides reported in fluids produced from other Marcellus Shale natural-gas wells and O&G wells in other unconventional shale formations (Table S3). 5,6,9,10,12,13,39 Among the 20 compounds identified here, only five have been previously identified in HF wastewaters, chlorinated methanes (e.g., trichloro-), halogenated decanes (including 1-chlorohexa-, 1-iodo-2-methylun-, and 1-iodotetra-), and benzyl chloride (Figure 1A), highlighting the utility of this nontargeted high-resolution mass spectrometery approach with these chemically complex samples. Haloalkanes are the most structurally diverse compounds identified here and by others, 10,40,41 and although this is unsurprising considering the large abundance of aliphatic compounds in black shales, 42 existing analytical methods would also bias toward their detection.…”
Section: ■ Results and Discussionmentioning
confidence: 80%
“…The backflow water from fracking has potential negative health effects through ingestion, inhalation, and dermal exposure because of contaminants such as Arsenic, Barium, Benzene, Copper, Lead, Thallium, Vinyl chloride, among others (Abualfaraj et al, 2018). Fracking sites have been found to infringe upon human rights and contribute to environmental injustices.…”
Section: Frackingmentioning
confidence: 99%